2002
DOI: 10.3136/fstr.8.85
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Process of Linoleic Acid Encapsulated with a Polysaccharide by Spray-Drying.

Abstract: The oxidation processes of linoleic acid encapsulated with gum arabic or maltodextrin at various weight ratios by spray-drying were analyzed using the model in which the free energy of activation for the rate constant of the autocatalytic type kinetics was assumed to obey a Gaussian distribution. The model could well express the oxidation processes, and the rate constant corresponding to the mean value of the free energy of activation, k, was greater for linoleic acid encapsulated at the higher weight ratio. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…Hence, having a technological procedure to provide oxidative protection in order to preserve the healthy components and quality attributes of walnut oil is a demanding topic in food industry. In that way, microencapsulation can be designed as a valid methodology to protect polyunsaturated fatty acid from light and heat damage, suppressing or retarding the oxidation (Fang, Shima, & Adachi, 2005;Ishido, Hakamata, Minemoto, Adachi, & Matsuno, 2002). Apart from that, microencapsulation has been used by the food industry to deliver ϖ-3 oils through food without detracting from its sensory properties (Sanguansri & Augustin, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Hence, having a technological procedure to provide oxidative protection in order to preserve the healthy components and quality attributes of walnut oil is a demanding topic in food industry. In that way, microencapsulation can be designed as a valid methodology to protect polyunsaturated fatty acid from light and heat damage, suppressing or retarding the oxidation (Fang, Shima, & Adachi, 2005;Ishido, Hakamata, Minemoto, Adachi, & Matsuno, 2002). Apart from that, microencapsulation has been used by the food industry to deliver ϖ-3 oils through food without detracting from its sensory properties (Sanguansri & Augustin, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…A stable emulsion with minimum droplet size can increase the retention of volatiles and shelf-life of encapsulated oil products through reduction of unencapsulated oil at the surface of powder particles (Ishido, Hakamata, Minemoto, Adachi, & Matsuno, 2002;Soottitantawat, Yoshii, Furuta, Ohkawara, & Linko, 2003. So, sub-micron emulsions can be of real benefit for encapsulation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the oxidative stability of the encapsulated lipid, such as the type of polyunsaturated fatty acid, kind of wall material, and weight ratio of the lipid to wall material, have been examined [5][6][7][8][9][10] . We reported that the oxidation proceeded more slowly for the linoleic acid encapsulated with maltodextrin in smaller oildroplets 7,8) . In these reports, the oil-droplet sizes in emulsions were on the orders of submicrometers or micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…This is a feature of the oxidation of encapsulated unsaturated fatty acid. 7,8) The change with time of the fraction of unoxidized methyl linoleate in the microcapsule, Y, was expressed by the following modified Weibull equation: (1) where Y ∞ is the unoxidized oil fraction at which the oxidation leveled off or practically ceased, t is the storage time, k is a rate constant and n is a shape constant. The Y ∞ value was evaluated by averaging the Y values for long storage periods, and the parameters, k and n, were then determined to best-fit the experimental results to using the Solver of Microsoft Excel for Windows.…”
mentioning
confidence: 99%